Strategies for the multimedia development of modern Russian media - Kolesnichenko А.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2025)
All the most popular Russian media sites are converged. This was shown by studies conducted in 2022-2024. However, the proportion of multimedia publications varies enormously, from single multimedia publications to the dominance of multimedia publications in the total volume of content. In this regard, we can talk about three strategies for the multimedia development of modern Russian media – exclusive, selective and total. With an exceptional strategy, multimedia elements are represented in a small part of the publications, but they complement these publications significantly. With selective multimedia, up to a third of publications are multimedia, and the most popular multimedia format is the addition of a news story with a reportage video. With total multimedia, multimedia publications on the site dominate, but a significant part of the multimedia is not related to the event covered in the text part, and is usually a background on the topic or a video news collection. The research results show that the Russian media has not yet developed a generally accepted multimedia strategy, and that the level of multimedia content is not a key factor influencing the popularity of the media.